Literature Review Of Authentication Layer For Public Cloud Computing: A Meta-Analysis - Eldow, Abdalla; Shakir, Mohanaad; Talab, Mohammed Ahmed; Muttar, Ahmed Kh.; Tawafak, Ragad M. (JATIT, 2019)
Cloud computing is a rapidly growing technology due to its highly flexible uses and applications. It also has other features such as simplicity, quick data access and reduced data storage costs. Consequently, it has been widely used by many organizations. This widespread use of cloud computing among organizations causes many security issues. Moreover, cloud computing layers are likely to be jeopardized by many security risks such as privileged user access, data location, data segregation, and data recovery. This paper aims to prepare an ample debate of a literature review-based studies that provided important insights to researchers in the scope of security cloud computing. The researcher applied a relevant set of keywords. These keywords are limited to the title, abstract and keywords search archives published between 2010 and June 2018. The database search returned a total of 308 publications. In addition, we conducted backward-forward searches from the reference lists of relevant, quality previous works on the security framework in public cloud computing studies. Then, the researcher filtered the publications to only full text access articles that were written in English only. Finally, this study obtained a many publication. The findings of this paper address many important points such as in this study is recommended to apply behavior recognition with password for improving authentication layer performance in cloud computing. This study finds most of current studies neglected the present of human factor in password-based authentication, and learnability in password-based authentication is highly weak. Despite this, very few studies have adopted the behavior recognition with password in public cloud.